The Influence of Zaha Hadid’s Roots and Heritage on her Architectural Approach - Azad Rauof, Tara Azad Rauof (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
In addition to her books, essays, interviews, and studies, Ms. Zaha Hadid was a remarkable architect known for her deconstructivism style, which has been called inventive, flamboyant, radical, and revolutionary. She thought that an architect is far more than just a Renaissance master. Zaha emphasized the significance of using architecture to infuse cultural values into society. She was the most qualified architect to be sent on that mission if that is how it should be. Her famous interpretation “It’s not about being nationalistic or patriotic; I cannot erase back the years I spent in Iraq. And I really enjoy the nation” evoked the central concept for this study. Does her architectural approach reflect her background? The research begins with a list of the pertinent aspects and characteristics of Islamic architecture, followed by a philosophical analysis of Zaha’s four proposed designs, two of which are intended to be built in Europe and the others in the Middle East, despite the fact that two enrollment were not chosen as a winner. The conflict between her style’s Eastern and Western inspirations has never been clearly established. By examining some of her designs in the Middle East and contrasting them with the components, and characteristics of Islamic architecture, in order to answer the question posed earlier.